Tailoring Consent to Context: Designing an Appropriate Consent Process for a Biomedical Study in a Low Income Setting - Tekola, Fasil; Bull, Susan J.; Farsides, Bobbie; Newport, Melanie J.; Adeyemo, Adebowale; Rotimi, Charles N.; Davey, Gail (PLOS Neglected Tropical Diseases, 2009)
Background Currently there is increasing recognition of the need for research in developing countries where disease burden is high. Understanding the role of local factors is important for undertaking ethical research in developing countries. We explored factors relating to information and communication during the process of informed consent, and the approach that should be followed for gaining consent. The study was conducted prior to a family-based genetic study among people with podoconiosis (non-filarial elephantiasis) in southern Ethiopia. Methodology/Principal Findings We adapted a method of rapid assessment validated in The Gambia. The methodology was entirely qualitative, involving focus-group discussions and in-depth interviews. Discussions were conducted with podoconiosis patients and non-patients in the community, fieldworkers, researchers, staff of the local non-governmental organisation (NGO) working on prevention and treatment of podoconiosis, and community leaders. We found that the extent of use of everyday language, the degree to which expectations of potential participants were addressed, and the techniques of presentation of information had considerable impact on comprehension of information provided about research. Approaching podoconiosis patients via locally trusted individuals and preceding individual consent with community sensitization were considered the optimal means of communication. Prevailing poverty among podoconiosis patients, the absence of alternative treatment facilities, and participants' trust in the local NGO were identified as potential barriers for obtaining genuine informed consent. Conclusions Researchers should evaluate the effectiveness of consent processes in providing appropriate information in a comprehensible manner and in supporting voluntary decision-making on a study-by-study basis.